Assessment of heavy metals and health risks of street vended foods in the Mangaung metro municipality, free State, South Africa - Letuka, Ponts’o; Nkhebenyane, Sebolelo Jane; Tywabi-Ngeva, Zikhona (Edelweiss Applied Science and Technology, 2025)
Street food vending is part of the informal sector that plays a significant role in improving the socio-economic status of vendors and the food security of consumers but faces safety challenges mostly due to anthropogenic activities and the lack of regulation. This study aimed to evaluate heavy metal contamination in commonly vended foods—pap, chicken, pork, and moroho/salads—in the Free State, South Africa, and assess the associated health risks to consumers. Shapiro-Wilk’s normality test and Kruskal-Wallis H tests were used to compare means. Results indicated heavy metal contamination in all analyzed samples. The overall median and IQR in descending order: Fe 4.365(4.424), Zn 3.605(3.711), As 2.653(2.971), Pb 1.095(1.266), Cu 0.271(0.326), Cr 0.212(0.117), and Zn 0.023(0.027) mg/kg. A significant difference (p < 0.05) was found for As between all pairs, while other heavy metals showed some variations without statistical significance. The EDI values of all sample types were below the recommended dietary values, suggesting that the heavy metals may not pose a public health risk. The health risk assessment through ICLR and Hazard Index (HI) indicated potential cancer and non-cancer risks from heavy metals in street-vended foods, as ICLR ≥ 10-3 and HI > 1. This implies that habitual consumers are at risk of non-carcinogenic health conditions.